Heritage buildings’ retrofitting according to ENERPHIT requirements - Dopierala, Magdalena (2015)
This thesis refers to the applying of Passive house concept to a old building from the early twentieth century in Polish climate, focusing on city of Jarocin. All work is based on the EnerPHit requirements for buildings retrofitting (Certification thermomodernization with approved quality using quality components for passive construction - EnerPHit) The aim of this study is to reach solutions to solve the problem of achiving low heating demand for old building in colder climate, according EnerPhit requirements. The study began with the introduction to Passive House concepts for new and retrofitted buildings. Therefore, the examples of construction solutions, materials and the thermal performance comparison between them have been described. The software “Passive House Planning Package” has been adopted for the thermal balance calculation. Summarizing, this study presents the Passive House concept for building retrofitting, which focus on an historical old building, located in central of Poland, and conclude for the possible achivement of this standard requirements.